2013
DOI: 10.1001/jamadermatol.2013.511
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Eczematous Eruptions in the Aging

Abstract: IMPORTANCEDermatologists frequently encounter patients of advanced age presenting with chronic eczematous eruptions of uncertain etiology. When a drug-induced cutaneous eruption is suspected, identifying the responsible drug(s) is a complex clinical challenge.OBJECTIVE To determine whether certain drug classes, and in particular calcium channel blockers, are associated with chronic eczematous eruptions in the aging (CEEA) in the United States.DESIGN Retrospective case-control study.SETTING Ambulatory patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 10 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Among antimicrobials, higher rates of pruritus with penicillin antibiotics and trimethoprim–sulfamethoxazole are thought to be secondary to inflammatory skin eruptions or cholestatic liver injury [1,3]. Among cardiovascular drugs, calcium channel blockers, beta blockers, and hydrochlorothiazide are associated with pruritus from skin inflammation, while itch with ACE inhibitors is thought to result from increased levels of bradykinin [3,6,7]. In addition, the rate of pruritus observed in statins (0.67%) is significant, considering its ubiquitous use as the second most commonly prescribed medication in the study (n = 316,196).…”
Section: Discussionmentioning
confidence: 99%
“…Among antimicrobials, higher rates of pruritus with penicillin antibiotics and trimethoprim–sulfamethoxazole are thought to be secondary to inflammatory skin eruptions or cholestatic liver injury [1,3]. Among cardiovascular drugs, calcium channel blockers, beta blockers, and hydrochlorothiazide are associated with pruritus from skin inflammation, while itch with ACE inhibitors is thought to result from increased levels of bradykinin [3,6,7]. In addition, the rate of pruritus observed in statins (0.67%) is significant, considering its ubiquitous use as the second most commonly prescribed medication in the study (n = 316,196).…”
Section: Discussionmentioning
confidence: 99%
“…However, two prior case-control studies noted a possible relationship of these medications with the development of chronic eczematous eruptions in the elderly [11, 12]. In the study by Summers et al [13], patients older than 50 years who were taking the drug for at least 1 month and suffered a chronic eczematous eruption for at least 2 months were more likely to be on CCBs and thiazides compared to controls who were patients with common dermatological conditions such as actinic keratosis, basal cell carcinoma, impetigo and seborrhoeic keratoses. In another study by Joly et al [12], patients older than 60 years who suffered from a chronic eczematous eruption affecting more than 20% of the body surface for at least 3 months were more likely to be on CCBs compared to controls who were patients in private dermatology practices and inpatients with non-dermatological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have shown a link between chronic use of antihypertensive drugs and the development of chronic eczematous eruptions in the elderly [12, 13]. They suggested that a proportion of these chronic eczematous eruptions could be attributed to the use of these chronic medications.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular drugs such as anticoagulants, methyldopa, statins, CCBs, and thiazides were also found to be associated with eczematous drug eruptions [ 13 ]. Heparin and telmisartan-hydrochlorothiazide have been reported to induce BS/SDRIFE [ 14 , 15 ].…”
Section: Eczematous Drug Eruptionmentioning
confidence: 99%